INFLUENCE TECHNIQUE VS IDEAL MODEL ON CREDIBILITY THEORY DISTRIBUTIONS RATIOS: A CASE STUDY OF TRIPLE JUMP - Mohammed, Zerf; Idris, Mokkedes Moulay; Ali, Bengoua; Nasreddin, Bendahmane Med (European Scientific Journal, ESJ, 2015)
The objective of this study is to describe and compare the techniques used by elite triple jumpers in the world to determine the impact of the modality distribution ratios in achieving results. Our subjects were the 2009-2011 global elite’s finalists with five (5) Algerian amateur athletes. In the absence of technological methods in Algeria, our study explores the reports (IAAF): 1. To describe the phase distribution of the practice model between our world champions (2009 and 2011) 2. To compare the credibility theory of distributions ratio achievement with the modality dominant techniques practiced by champions (2009 and 2011). 3. To answer this question: can we consider the phase difference ratios as a bad distribution error in the technical ideal? As a result, we chose the analysis of variance and the correlation of relative distances obtained from each phase of the official distance achieved by the athlete. For the study statistics, our used data is based on the "t" independent method compared to the impact phase distributions (hop, step, and jump) charged with the results achieved in the test. However, our goal for this research is: • Using biomechanics to determine errors and integrate the modern scientific methods in monitoring the athletic program. • To allow our elites and their coaches to examine the impact of modality distribution ratios in achieving results in order to choose the good combined efforts and the selected template model practiced to improve the best performance in training and competition.